Innovation, Incubation and Entrepreneurship Case Studies from IIT Kanpur - Phani, B. V.; Khandekar, Sameer; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book focuses on promoting entrepreneurial ecosystems within universities and educational institutes. It especially emphasizes the thriving systems and practices existing within the Indian Institute of Technology Kanpur (IITK). It discusses cases and successes of the SIDBI Incubation and Innovation Centre in the Institute. This edited volume highlights the vision of IITK and describes a few of the major achievements of the past few years. It especially showcases the requirements and challenges of creating, sustaining, and boosting such entrepreneurial ecosystems and incubation centres. The contents of this book will be useful to researchers, administrators, and corporate collaborators working in the area of monetizing technology coming from educational institutions by converting it to successful products and business ideas. .
1. The 4 I's of Innovation -- 2. Winds of Change -- 3. The Role of Experimentation in Fostering Innovation -- 4. The Game Changers - Seekers to Creators -- 5. Lab to Market: A Case Study -- 6. Withering to Weathering - A Farmers' Friend -- 7. Bridging the Technology Gap: Linking IITs with ITIs -- 8. Manning the Unmanned - The Aarav Story -- 9. Innovation and Entrepreneurship Ecosystem at IIT Kanpur - A Serendipitous Journey.
Keywords: Industrial engineering; Production engineering; Technological innovations; Technical education; Engineering design; Entrepreneurship; New business enterprises; Industrial and Production Engineering; Innovation and Technology Management; Engineering and Technology Education; Engineering Design; Entrepreneurship